Radial-velocity measurements of subdwarf B stars - Copperwheat, C. M.; Morales-Rueda, L.; Marsh, T. R.; Maxted, P. F. L.; Heber, Ulrich; Heber, Ulrich (Monthly Notices of the Royal Astronomical Society, 2011)
Subdwarf B (sdB) stars are hot, subluminous stars which are thought to be core-helium burning with thin hydrogen envelopes. The mechanism by which these stars lose their envelopes has been controversial, but it has been argued that binary star interaction is the main cause. Over the past decade we have conducted a radial-velocity study of a large sample of sdB stars, and have shown that a significant fraction of the field sdB population exists in binary systems. In 2002 and 2003, we published 23 new binary sdB stars and the definitions of their orbits. Here, we present the continuation of this project. We give the binary parameters for 28 systems, 18 of which are new. We also present our radial-velocity measurements of a further 108 sdBs. Of these, 88 show no significant evidence of orbital motion. The remaining 20 do show radial-velocity variations, and so are good candidates for further study. Based on these results, our best estimate for the binary fraction in the sdB population is 46-56per cent. This is a lower bound since the radial-velocity variations of very long period systems would be difficult to detect over the baseline of our programme, and for some sources we have only a small number of measurements. © 2011 The Authors Monthly Notices of the Royal Astronomical Society © 2011 RAS.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: close; Binaries: spectroscopic; Subdwarfs